Acquired lymphangiectasis following surgery and radiotherapy of breast cancer - Angoori Gnaneshwar Rao (Wolters Kluwer Medknow Publications, 2015)
Acquired lymphangiectasia (AL) is a significant and rare complication of surgery and radiotherapy. We report lymphangiectasia in a 40-year-old woman who had undergone radical mastectomy and radiotherapy. After 4 years of combined therapy, she developed multiple vesicles and bullae. Skin biopsy confirmed the diagnosis of lymphangiectasia. The case is unique as it is not associated with lymphedema, which is a usual accompaniment of lymphangiectasia following surgery and radiotherapy. AL is usually asymptomatic, but trauma may cause recurrent cellulitis. Treatment modalities include electrodessication, surgical excision, sclerotherapy and carbon dioxide laser ablation.